Bioorganic fertilizer promotes pakchoi growth and shapes the soil microbial structure - Wang, Tao; Cheng, Keke; Huo, Xingjuan; Meng, Pinpin; Cai, Zhonghua; Wang, Zongkang; Zhou, Jin (Frontiers in Plant Science, 2022)
As a functional probiotic, Bacillus subtilis can promote crop growth and improve nutrient utilization by various mechanisms, so it has been made into bioorganic fertilizer as a replacement for chemical fertilizer. However, the effects of B. subtilis bioorganic fertilizer application on the yield and quality of commercial crops of Brassica chinensis L., the soil physicochemical properties and the microflora have not been clarified. In this study, pot experiments were conducted using Brassica chinensis L. plants with four fertilization treatments: control without fertilization (CK), chemical fertilizer (CF), organic fertilizer (OF), and bioorganic fertilizer containing B. subtilis (BF). After 30 days of pot experiment, the results showed that BF efficiently improved plant height and biomass (1.20- and 1.93-fold, respectively); as well as significantly increasing soil available potassium and pH value. Using high-throughput sequencing, we examined the bacterial and fungal communities in the soil, and found that their diversity was remarkablely reduced in the BF treatment compared to CK group. A principal coordinate analysis also showed a clear separation of bacterial and fungal communities in the BF and CK groups. After application of B. subtilis bioorganic fertilizer, some beneficial bacteria (such as Bacillus and Ammoniphilus) and fungi (Trichoderma and Mortierella) were enriched. A network analysis indicated that bacteria were the dominant soil microbes and the presence of B. subtilis stimulated the colonization of beneficial microbial communities. In addition, predictive functional profiling demonstrated that the application of bioorganic fertilizer enhanced the function of mineral element metabolism and absorption and increased the relative abundance of saprotrophs. Overall, the application of bioorganic fertilizer effectively changed the soil microflora, improved the soil available potassium and pH value, and boosted the yield of Brassica chinensis L. This work has valuable implications for promoting the safe planting of facility vegetables and the sustainable development of green agriculture.